2008
DOI: 10.1901/jaba.2008.41-579
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Group Contingency Management for Cocaine‐dependent Methadone Maintenance Patients

Abstract: Contingency management (CM) for drug abstinence has been applied to individuals independently even when delivered in groups. We developed a group CM intervention in which the behavior of a single, randomly selected, anonymous individual determined reinforcement delivery for the entire group. We also compared contingencies placed only on cocaine abstinence (CA) versus one of four behaviors (CA, treatment attendance, group CM attendance, and methadone compliance) selected randomly at each drawing. Two groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Clinicians would like to target more than one behavior simultaneously (e.g. attendance and abstinence) and some prior research has suggested ways that more than one behavior might be addressed without significant drops in efficacy (e.g., Ghitza et al, 2008; Kirby et al, 2008; Petry & Martin, 2002). Addressing multiple behaviors may improve implementation of CM.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians would like to target more than one behavior simultaneously (e.g. attendance and abstinence) and some prior research has suggested ways that more than one behavior might be addressed without significant drops in efficacy (e.g., Ghitza et al, 2008; Kirby et al, 2008; Petry & Martin, 2002). Addressing multiple behaviors may improve implementation of CM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tokens can be given and never removed (Drabman, Spitalnik, & Spitalnik, 1974;Kirby, Kerwin, Carpenedo, Rosenwasser, & Gardner, 2008;. The teacher may present a token each time a desired behavior occurs and never remove tokens when an undesired behavior occurs.…”
Section: Token Economiesmentioning
confidence: 99%
“…Another example of behavioral technology is a group contingency (Gresham & Gresham, 1982; Kirby, Kerwin, Carpenedo, Rosenwasser, & Gardner, 2008; Williamson, Williamson, Watkins, & Hughes, 1992). A group contingency is arranged when consequences (e.g., vouchers exchangeable for goods and services) are delivered to each member of a group only if all members of the group meet a specified criterion.…”
mentioning
confidence: 99%